Direct inhibitory rffect of the phosphodiesterase-4 inhibitor, roflumilast, on neutrophil migration in COPD - Dunne,A; Kawamatawong,T; Fenwick,P; Davies,C; Tullett,H; Barnes,P; Donnelly,L (American Journal of Respiratory Cell and Molecular Biology, 2019)
Neutrophilic inflammation is characteristic of COPD, yet there are no effective anti-inflammatory therapies. The phosphodiesterase (PDE)4 inhibitor, roflumilast is approved for use in COPD and suppresses sputum neutrophilia. The mechanism underlying this observation is unclear and therefore this study addressed whether roflumilast directly affected neutrophil migration. Blood-derived neutrophils were isolated from non-smokers, smokers and COPD patients and chemotaxis measured using Boyden chambers. Intracellular calcium ion concentration ([Ca2+]i) was measured by fluorimetry and shape change and CD11b expression by flow cytometry. Neutrophils from COPD patients showed enhanced chemotactic responses towards both CXCL1 and LTB4 compared with control cells. Chemotaxis was inhibited by both the active metabolite, roflumilast-N-oxide, and rolipram in a concentration-dependent manner with no difference in responsiveness between subjects. Roflumilast-N-oxide and rolipram were less efficacious against CXCL1 and LTB4-mediated [Ca2+]i suggesting that inhibition was not via this pathway. Both PDE4 inhibitors attenuated chemoattractant-mediated shape change and CD11b up-regulation suggesting common mechanisms. The stable cAMP analogue, 8-Br-cAMP, inhibited chemotaxis, as did the direct Epac1 activator 8-pCPT-2’-O-Me-cAMP but not the direct PKA activator, 6-Bnz-cAMP. These data suggest that roflumilast inhibits neutrophil chemotaxis directly via a cAMP-mediated mechanism requiring activation of Epac1, and that Epac1 activators could reduce COPD neutrophilic inflammation.